Prognosis of Pregnancies with Different Degrees of Glucose Intolerance - Sevgi Ayhan; Sündüz Özlem Altınkaya; Tayfun Güngör; Utku Özcan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The purpose of the present study was to evaluate the effect of different degrees of glucose intolerance on maternal and perinatal outcomes. STUDY DESIGN: Retrospective data of 500 singleton pregnancies screened for gestational diabetes mellitus were reviewed. Maternal and perinatal outcomes for four different groups were compared. First group consisted of patients with normal 50-g test, second group was formed by patients with abnormal 50-g test but a normal 100-g test. Third group included patients with one abnormal value after 100-g test. Patients in the fourth group were diagnosed to have gestational diabetes mellitus with two or more abnormal values after 100-g test. RESULTS: Macrosomia, neonatal intensive care unit admission and preterm premature rupture of membranes were the highest in the group with one elevated value after glucose tolerance test. Preterm labor was the highest in the gestational diabetes group. The difference in the rate of preeclampsia, polyhydramnios, neonatal hypoglycemia and hypocalcemia was not statistically significant (p>0.05). CONCLUSION: Although women with one elevated value after glucose tolerance test are not diagnosed with gestational diabetes mellitus, they are still at risk for adverse maternal and perinatal outcomes. They seem to be prone to develop obstetric complications related to glucose intolerance and should be followed up carefully during the antepartum and intrapartum period.